1988
DOI: 10.1063/1.340044
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of ZnS thin films by intense pulsed ion beam

Abstract: The crystallographic and electroluminescent characteristics of ZnS:Mn thin films prepared by radio frequency ion plating technique J. Vac. Sci. Technol. A 8, 43 (1990); 10.1116/1.576416 Preparation and characterization of ZnS thin films produced by metalorganic chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…However, it is already reported that intense pulsed-ion beam evaporation (IBE) method enables us to deposit crystallized boron-carbide thin films without substrate heating and post annealing [5]. IBE is newly developed high-speed thin film deposition process [6,7]. High density ablation plasma produced by irradiation of pulsed ion-beam onto the target is solidified on the substrate and thin film with almost the same composition as that of target is formed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is already reported that intense pulsed-ion beam evaporation (IBE) method enables us to deposit crystallized boron-carbide thin films without substrate heating and post annealing [5]. IBE is newly developed high-speed thin film deposition process [6,7]. High density ablation plasma produced by irradiation of pulsed ion-beam onto the target is solidified on the substrate and thin film with almost the same composition as that of target is formed.…”
Section: Introductionmentioning
confidence: 99%
“…For thin film preparation by IBE, a pulse power generator ('ETIGO-II') with a magnetically insulating ion diode [15] was used. A cathode and an anode were placed in a chamber which was evacuated to a pressure of 1 x 10 -4 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, however, these ion beams with ion energies from 50 keV to 10 MeV, ion currents from 1 kA to 10 MA, and pulse durations from 10 to 1000 ns have been finding new applications in diverse fields such as materials processing [4], [5]. Because of the short range of the ions in matter, its application usually involves the surface modification of materials, e.g., implantation [6], alloy mixing [7], [8], defect formation [9], [10], and thin-film deposition [11], [12]. For many of these applications, these beams are used primarily as heat sources to ablate or rapidly melt solid targets.…”
Section: Introductionmentioning
confidence: 99%